Meningkatkan Hasil Belajar Matematika Menggunakan Model Problem Based Learning Materi Volume Balok Kelas V UPTD SDN Kurau Kabupaten Tanah Laut - M. Rizki; Sunarno (Jurnal Pendidikan Sosial Dan Konseling, 2024)
In this study, the problem lies in the fact that students tend to be passive and do not ask questions when learning mathematics with the material of the volume of space, namely blocks. When the teacher asks students questions, they only answer with the answers that are already listed in the book. Students tend to answer based on what they remember and what they know. Researchers tried to find solutions to these problems by using a learning model called problem-based learning. The research approach used in this study is qualitative research, namely action research. The types of data presented in this research are quantitative and qualitative data. Observations with observation sheets provide qualitative data about teacher and student activities during the teaching and learning process. Students' learning outcomes, measured by written tests at the end of each session, provide quantitative data. At UPTD SDN Kurau, this research took place in the even semester of Class V in the 2023/2024 school year. The results showed that teacher, student activities and learning outcomes improved in each cycle with the categories "Very Active" and "Completed" after the action research process was carried out for two meetings in the class. This shows that the problem-based learning model describes successful learning.